Estimating Long-Term Expected Returns - Ma R; Marshall BR; Nguyen NH; Visaltanachoti N (Taylor and Francis Group, 2024)
Estimating long-term expected returns as accurately as possible is of critical importance. Researchers typically base their estimates on yield and growth, valuation, or a combined yield, growth, and valuation (“three-component”) framework. We run a horse race of the abilities of different frameworks and input proxies within each framework to estimate 10- and 20-year out-of-sample returns. The three-component model based on the TRCAPE valuation proxy outperforms estimates based on historical mean benchmark returns, with mean square error improvements exceeding 30%. Using this approach in asset allocation decisions results in an improvement in Sharpe ratios of more than 50%.
Keywords: asset allocation; long-term expected returns; three-component model; valuation